2017
DOI: 10.3133/sir20175022p
|View full text |Cite
|
Sign up to set email alerts
|

Geologic field-trip guide to the volcanic and hydrothermal landscape of the Yellowstone Plateau

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit https://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…These authors also showed that the Ge/Si ratio of solutions in equilibrium with Ge‐bearing silicates may vary strongly with temperature due to the significant differences in the enthalpies of formation and heat capacities of Ge(OH) 4 and Si(OH) 4 . The significantly higher Ge/Si ratios of UGB's alkaline‐chloride waters (183 ± 22 µmol.mol −1 ) compared to the values reported for the acid‐sulfate springs close to Yellowstone Lake (57 ± 54 µmol.mol −1 , n = 69; Gemery‐Hill et al., 2007) may point to higher subsurface temperatures of the former type of thermal waters (>150°C, Hurwitz et al., 2016) relative to the latter ones (<150°C, Morgan et al., 2017). Pokrovski and Schott (1998) also concluded that the mobility in alkaline solution of Ge is enhanced compared to that of Si because Ge(OH) 4 dissociates at lower pH values than Si(OH) 4 .…”
Section: Discussionmentioning
confidence: 83%
“…These authors also showed that the Ge/Si ratio of solutions in equilibrium with Ge‐bearing silicates may vary strongly with temperature due to the significant differences in the enthalpies of formation and heat capacities of Ge(OH) 4 and Si(OH) 4 . The significantly higher Ge/Si ratios of UGB's alkaline‐chloride waters (183 ± 22 µmol.mol −1 ) compared to the values reported for the acid‐sulfate springs close to Yellowstone Lake (57 ± 54 µmol.mol −1 , n = 69; Gemery‐Hill et al., 2007) may point to higher subsurface temperatures of the former type of thermal waters (>150°C, Hurwitz et al., 2016) relative to the latter ones (<150°C, Morgan et al., 2017). Pokrovski and Schott (1998) also concluded that the mobility in alkaline solution of Ge is enhanced compared to that of Si because Ge(OH) 4 dissociates at lower pH values than Si(OH) 4 .…”
Section: Discussionmentioning
confidence: 83%
“…The 75-km by 45-km Yellowstone Caldera formed during the most recent of these eruptions about 631 ka (Christiansen, 2001;Matthews et al, 2015). The caldera hosts two resurgent domes, the Sour Creek dome and Mallard Lake dome (Figure 1), and it is largely filled by rhyolite lava flows that range in age from shortly after caldera formation to as young as 70 ka (Christiansen, 2001;Morgan et al, 2017). Today the Yellowstone Caldera is among the world's most active in terms of seismicity, thermal features, gas emissions, and surface deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The inset map in the bottom right shows the locations of the Norris-Hebgen seismic belt (labeled N-H) and the Norris-Mammoth corridor (labeled N-M) eruptions. The Norris-Hebgen seismic belt is a rift-like zone of NNE-SSW extension (Savage et al, 1993; that is a site of minor postcaldera volcanism (Christiansen, 2001;Morgan et al, 2017). The belt extends west from near NGB to the site of the 1959 M s (surface wave magnitude) 7.5 Hebgen Lake earthquake (a few kilometers north of Hebgen Lake; Figure 1), and it is the zone of densest seismicity within the Park (Waite & Smith, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Yellowstone hydrothermal system is related to the most recent caldera eruption, but the hydrothermal fluids likely flow through rocks as old as Archean crystalline basement. The oldest prevolcanic rocks around the Yellowstone Plateau include Archean (3.5 to 2.5 Ga) Beartooth Province granitoids and schists (Christiansen and Blank 1972;Christiansen 2001;Hurwitz and Lowenstern 2014;Morgan et al 2017). Paleozoic and Mesozoic sedimentary rocks are also probably present in the subsurface.…”
Section: Regional Geologymentioning
confidence: 99%